Social media retrieval and mining : ADMA 2012 Workshops, SNAM 2012 and SMR 2012, Nanjing, China, December 15-18, 2012. Revised Selected Papers - Wu, Zhiang (Communications in Computer and Information Science,, 2013)
This book constitutes the refereed proceedings of the ADMA 2012 Workshops: The International Workshop on Social Network Analysis and Mining, SNAM 2012, and the International Workshop on Social Media Mining, Retrieval and Recommendation Technologies, SMR 2012, Nanjing, China, in December 2012. The 15 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on networks and graphs processing; social Web; social information diffusion; social image retrieval and visualization.